Nelson Mandela in his Own Words : From Freedom to the Future : Tribute and Speeches - Mandela, Nelson, 1918-2013; Edited by Asmal, Kader ; Chidester, David and James, Wilmot (London Abacus, 2013)
The speeches of Nelson Mandela
Include Illustration and Index
Keywords: Mandela, Nelson, -- 1918- -- South Africa -- Politics and government -- 20th century